Analisis Aparat Pengawasan Intern Pemerintah Terhadap Kualitas Laporan Keuangan Pemerintah Daerah Se- Indonesia - andi ramadhan, Syahrul; Wijaya, Henryanto (Jurnal Liabilitas, 2025)
This study aims to test and analyze the role of government internal supervisory apparatus (APIP) on the quality of financial reports of regency and city local government throughout Indonesia, especially the effect of APIP capability, SPIP maturity and the follow-up on audit recommendations on the quality of local government financial reports (LKPD). This research was conducted at regency and city local governments throughout Indonesia, using data from 2018-2021. The data analysis method used Partial Least Square (PLS) with the help of WarpPLS software. The results of this study indicate that partially APIP capability, SPIP Maturity and the follow-up on audit recommendations have a positive effect on the quality of regency and city local government financial reports and simultaneously APIP capability, SPIP Maturity and the follow-up on audit recommendations also have a positive effect on the quality of local government financial reports.